RABP: Delay/disruption tolerant network routing and buffer management algorithm based on weight - Hezhe Wang; Guangsheng Feng; Huiqiang Wang; Hongwu Lv; Renjie Zhou (International Journal of Distributed Sensor Networks)
Delay/disruption tolerant network is a novel network architecture, which is mainly used to provide interoperability for many challenging networks such as wireless sensor network, ad hoc networks, and satellite networks. Delay/disruption tolerant network has extremely limited network resources, and there is typically no complete path between the source and destination. To increase the message delivery reliability, several multiple copy routing algorithms have been used. However, only a few can be applied efficiently when there is a resource constraint. In this article, a delay/disruption tolerant network routing and buffer management algorithm based on weight (RABP) is proposed. This algorithm estimates the message delay and hop count to the destination node in order to construct a weight function of the delay and hop count. A node with the least weight value will be selected as the relay node, and the algorithm implements buffer management based on the weight of the message carried by the node, for efficiently utilizing the limited network resources. Simulation results show that the RABP algorithm outperforms the Epidemic, Prophet, and Spray and wait routing algorithms in terms of the message delivery ratio, average delay, network overhead, and average hop count.